The Effectiveness of Accelerated Problem Based Learning With Dynamic Assessment in Achieving Problem-Solving Skills - Ratri Rahayu; Kartono Kartono; Dwijanto Dwijanto; Arief Agoestanto (Universitas Negeri Semarang, 2022)
This research aims to analyzed the effectiveness of Accelerated Problem Based Learning (A-PBL) with dynamic assessment on students' problem-solving skills. This quantitative research had 319 students from the eighth grade of junior high school. The researchers took the sample with a random sampling technique. The results were 32 students for the experimental group. These learners received the A-PBL model with dynamic assessment. The other 32 students for the control group received a direct instruction model. The research instruments were a problem-solving skill test. The data were analyzed by descriptive statistical analysis and then continued with hypothesis testing. The hypothesis tests were independent sample t-test, one-sample t-test, proportional test, and simple linear regression test. The results showed that the A-PBL model is effectively used to achieve problem solving skills with indicators: (1) the learners' mathematic problem-solving skills taught by A-PBL with dynamic assessment met 65 score; (2) the average of learners' mathematics problem-solving skills taught by the A-PBL model and dynamic assessment was higher than the problem-solving skills of learners taught by the direct learning model; and (3) the proportion of students who have completed A-PBL learning with dynamic assessment is more than the proportion of students who have been taught using the direct instruction model. Research contributes scientifically to the development of learning model syntax that can be used to improve problem solving.